COVID-19 PANDEMIC REVIEW IN KUTUB SITTAH METHODS FOR UNDERSTANDING PANDEMICS IN THE BOOK OF POLAR SITTAH AND ITS SHARIA - Rachmawati (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
This study is based on the emergence of the Covid-19 pandemic which has claimed tens of thousands of lives in 2020. From an Islamic perspective, the phenomenon of the COVID-19 pandemic is believed to have a strong relevance to the hadiths of plague as once expressed by the Prophet Muhammad 1400 years ago. The main indicator in this study is to examine and directly search for hadiths in the Kutub Sittah, especially tracing the hadiths of the Prophet that mention the plague, specifically in the hadiths of the Prophet stating plague as a plague that is the same as the Covid-19 virus that has hit modern society. After tracing the hadiths of the Prophet that mention the plague by identifying the hadiths of plague specifically in the Kutub Sittah, the purpose of this study is to determine the quality and status of the hadiths about plague contained in the Kutub Sittah, then to find out the relevance of understanding the hadiths of plague in the Kutub Sittah with the Covid-19 pandemic. In the end, the research results show that the Covid-19 pandemic is the same as what the Prophet described in his various sayings about the hadiths of the plague